Neuropathology of cerebral arteriovenous malformations in children. Issue 5 (May 1980) - Takashima, S; Becker, L E
Abstract : Neuropathological findings in children who had died of cerebral arteriovenous malformation under 6 years of age were contrasted with those of children aged 6 to 15 years. In all subjects, the abnormalities were more marked in the shunting vessels and veins distal to the arteriovenous shunt than in the arteries. Fibrous thickening, calcification an adherent thrombus of vessel wall, and gliosis and haemosiderin in contiguous neural tissue were more common in the older than the younger children. Children less than 1 week old with vein of Galen malformations presented with congestive heart failure and "watershed" cerebral infarction; most of those over one week old had hydrocephalus and venous thrombosis with haemorrhagic infarction.